Our industrial and reformatory school systems in relation to the poor - Daly, E.D. (Statistical and Social Inquiry Society of Ireland, 1891)
My purpose in bringing it before you can only be to refresh our minds on a subject of importance, apt to be somewhat overlooked in the rush of politics around us. It is a subject on which a great deal of learning can be brought to bear, from theories of high philosophy, to the numerical arguments of statistics; but it can also be approached from points of view which involve no learning beyond such as may be acquired by most of us, who in the homely duties of life gain some practical knowledge of human nature. From such a standpoint the discussion must consist chiefly in generalizing from those principles and tendencies of human conduct which everyday life tests and illustrates.
Read Tuesday, 17th March, 1891
Keywords: Reformatory schools; Poverty relief; Industrial schools; 314.15